RREB1-mediated SUMOylation enhancement promotes chemoresistance partially by transcriptionally upregulating UBC9 in colorectal cancer - Deng, Ya-nan; Chen, Ying; Gao, Shan; Zhang, Nan; Luo, Yinheng; Luo, Shu; Li, Qiu; Fu, Xianghui; Liang, Shufang (Frontiers in Pharmacology, 2024)
Chemoresistance is a main cause of chemotherapy failure and tumor recurrence.The effects of global protein SUMOylation on chemoresistance in colorectal cancer (CRC) remains to be investigated. Herein, we have proposed that the elevated SUMO2/3-modified proteins confer 5-fluorouracil (5-FU) chemoresistance acquisition in CRC. The SUMOylation levels of global proteins in CRC cell lines were elevated compared with normal colon cell line NCM460. 5-FU treatment obviously reduced SUMOylation of global proteins in 5-FU-sensitive CRC cells including HT29, HCT116 and HCT-8. However, in 5-FU-resistant HCT-8/5-FU cells, the expression level of SUMO2/3-modified proteins was increased under 5-FU exposure in a concentration-dependent manner. 5-FU treatment combined with SUMOylation inhibitor ML-792 significantly increased the sensitivity of 5-FUresistant cells to 5-FU and reduced colony formation numbers in HCT-8/5-FU cells.And UBC9-mediated SUMOylation elevation contributes to 5-FU resistance in HCT116 cells. Moreover, we also identified RREB1 as a regulator of SUMOylation profiling of global cellular proteins via directly binding to the promoter of UBC9.Overexpression of RREB1 promoted 5-FU resistance in CRC, which was partially abolished by treatment of inhibitor ML-792. In conclusion, RREB1-enhanced protein SUMOylation contributes to 5-FU resistance acquisition in CRC.